Probing photoprotection properties of lipophilic chain conjugated thiourea-aryl group molecules to attenuate ultraviolet-A induced cellular and DNA damages - Sobia Rana; Noor Fatima; Sana Yaqoob; Abdul Hameed; Munazza Raza Mirza; Almas Jabeen; Jamshed Iqbal (Scientific Reports, 2022)
Abstract Ultraviolet-A (UVA) radiation is a major contributor to reactive oxygen species (ROS), reactive nitrite species (RNS), inflammation, and DNA damage, which causes photoaging and photocarcinogenesis. This study aimed to evaluate the UVA protective potential of lipophilic chain conjugated thiourea-substituted aryl group molecules against UVA-induced cellular damages in human dermal fibroblasts (BJ cell line). We tested a series of nineteen (19) molecules for UVA photoprotection, from which 2′,5′-dichlorophenyl-substituted molecule DD-04 showed remarkable UVA protection properties compared to the reference (benzophenone). The results indicate that DD-04 significantly reduced intracellular ROS and nitric oxide (NO) as compared to the UVA-irradiated control (p < 0.001). Moreover, the compound DD-04 showed anti-inflammatory activity as it significantly reduced the levels of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) pro-inflammatory cytokines produced by THP-1 (human monocytic) cells (p < 0.05). DNA damage was also prevented by DD-04 treatment in the presence of UVA. It was observed that DD-04 significantly reduced the number of cyclobutane pyrimidine dimers (CPDs) when compared to the UVA-irradiated control (p < 0.001). Finally, the DNA strand breaks were checked and a single intact DNA band was seen upon treatment with DD-04 in the presence of UVA. In conclusion, DD-04 can be considered a potential candidate UVA filter due to its photoprotective potential.